Modeling humidity and stress-dependent subgrade soils in flexible pavements. (April 2020) - Peng, Junhui; Zhang, Junhui; Li, Jue; Yao, Yongsheng; Zhang, Anshun
Abstract: This study aimed to develop a finite element model to simulate the flexible pavement structure by considering the nonlinear characteristics of subgrade soils which are related to humidity and stress. First, an analytical model was proposed and proven to quantify the effect of the humidity and stress on the resilient modulus of subgrade soils. Second, a UMAT was programmed to characterize nonlinear moisture and stress-sensitive relationship of subgrade soils. Then, the humidity field values of subgrade were calculated by GEOSTUDIO and verified by field measurement. Meanwhile, the humidity field values were imported into ABAQUS through MATLAB. Finally, the UMAT was implemented in the finite element model of flexible pavement structures. The finite element simulation indicated that the distribution of moisture content of subgrade significantly affects the resilient modulus distribution of subgrade and critical response of pavement structures. Resilient modulus of subgrade soils in the vicinity of load area are significantly larger than those far away the load area. The surface deflection, the tensile stress at the bottom of inorganic binder base, and the compressive strains on the top of subgrade increase greatly with the initial humidity field condition to the equilibrium humidity field condition.